1981
DOI: 10.1172/jci110121
|View full text |Cite
|
Sign up to set email alerts
|

Increased Thirst and Plasma Arginine Vasopressin Levels during 2-Deoxy-d-glucose-induced Glucoprivation in Humans

Abstract: A B S T R A C T Insulin-induced hypoglycemia by unknown mechanism(s) increases plasma arginine vasopressin (AVP) levels in humans. Mechanisms for increased AVP levels during central nervous system glucoprivation were investigated by administering 20-min i.v. infusions of 2-deoxy-D-glucose (50 mg/kg), a competitive inhibitor of glucose utilization, or normal saline (sham), to 24 normal volunteers. Some of the infusions were administered in combination with neuropharmacological blocking agents (placebo). The beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 34 publications
(46 reference statements)
1
12
0
Order By: Relevance
“…The vasopressin data are consistent with previous preclinical (Baylis and Robertson, 1980b) and clinical (Thompson et al, 1981) secretion following 2DG administration. The lack of a significantly greater absolute vasopressin response in schizophrenic patients and its dissociation from the response of the exaggerated PA axis (Elman et al, 1998) may be related to patients in this study presenting no symptoms of polydipsia and hyponatremia, suggesting that they may not have abnormalities in the stressrelated vasopressinergic function.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The vasopressin data are consistent with previous preclinical (Baylis and Robertson, 1980b) and clinical (Thompson et al, 1981) secretion following 2DG administration. The lack of a significantly greater absolute vasopressin response in schizophrenic patients and its dissociation from the response of the exaggerated PA axis (Elman et al, 1998) may be related to patients in this study presenting no symptoms of polydipsia and hyponatremia, suggesting that they may not have abnormalities in the stressrelated vasopressinergic function.…”
Section: Discussionsupporting
confidence: 89%
“…independent of peripheral osmotic and/or haemodynamic changes) hypothalamic stimulus for vasopressin secretion (Baylis and Robertson, 1980a,b;Baylis et al, 1981;Thompson et al, 1981;Chiodera et al, 1992) and (ii) unlike cognitive stressors, it is not associated with performance bias, so that equal 'amounts' of perturbation are induced in both cognitively impaired patients with schizophrenia and healthy control subjects. Although this kind of metabolic stress may be distinct from the environmental stress implicated in exacerbation of psychosis (Jansen and Gispen-de Wied, 2000), it may provide unique information pertaining to general stress and limbic responsiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Even though a direct action of insulin at the hypothalamic level has been reported [4][5][6][7], normoglycemic hyperinsuliné mie clamp studies have demonstrated that hyperinsuline mia does not promote vasopressin secretion [8], There fore, the AVP and OT responses during an insulin toler ance test (ITT) are supposed to follow direct stimulation of hypothalamic glucoreceptors [4][5][6][7] elicited by the neuropenic symptomatic stimulus [9][10][11][12]. Recent studies This work was supported in part by a 'Ministcro Pubblica Received: Istruzionc* grant and by Bayer Italiana s.p.a.…”
Section: Introductionmentioning
confidence: 99%
“…In more than 100 reported 2DG tests (50 mg/kg) in normal adult subjects, the average increase of plasma glucose has been approximately 90 mg/dl (1,7,13,23,25,36,38,39,40). The lowest increase reported among 18 individual normal adult subjects was 26 mg/dl (23,38,39).…”
Section: Discussionmentioning
confidence: 99%